(untitled) (Research, Society and Development, 2022)
With the COVID-19 pandemic, companies needed to innovate to stay in the market, and digital marketing was a means to contribute to improving sales and increasing the visibility of organizations in the market. Therefore, this research aims to analyze how digital marketing can boost sales in a lingerie store. Regarding the methodology, the research is classified as exploratory quantitative, being applied a questionnaire with closed questions to a non-probabilistic sample of customers and potential customers of the company under study. After analyzing the results found, it can be observed that most respondents highlighted that the most used means of communication to find new stores is Instagram and that they buy in the store due to the variety of products and the good price or quality. The data indicate that the store achieves greater visibility through digital means and that the use of digital marketing contributes to increased sales of products, with customers saying that the quality of the photo of the products totally interferes with the choice. Therefore, the importance of investing in digital marketing is emphasized, seeking to improve the relationship between company and customer, and consequently increase the organization’s position in the current competitive market.